Hydrological Basis and Discipline System of Cryohydrology: From a Perspective of Cryospheric Science - Ding, Yongjian; Zhang, Shiqiang; Chen, Rensheng; Han, Tianding; Han, Haidong; Wu, Jinkui; Li, Xiangying; Zhao, Qiudong; Shangguan, Donghui; Yang, Yong; Liu, Junfeng; Wang, Shengxia; et al. (Frontiers in Earth Science, 2020)
Initially, cryohydrology was referred to as hydrology involving low temperatures, for example, the hydrological study of snow, ice, frozen ground, and cold water. This discipline broadened with the development of cryospheric science and now involves hydrological processes of various cryosphere elements systematically coupled with river basin hydrological processes. However, limited studies have introduced the characteristics and discipline connotations of cryohydrology from a perspective of cryospheric science. Here, we reviewed the evolution of the connotations of cryohydrology and analyzed its hydrological basis and discipline system. Three major conclusions were drawn. (1) Cryohydrology was developed based on traditional hydrology for a single element of the cryosphere and focuses on the hydrological functions of the cryosphere and its impact on the water cycle and water supply to other spheres. (2) The hydrological basis of cryohydrology can be summarized as water conservation, runoff recharge, and hydrological regulation. In detail, the water conservation function is primarily expressed as “source of freshwater” and “cold and wet islands,” the runoff recharge function is concerned with water supply, and the regulation function is effective at intra- and inter-annual scales. (3) The core research issues of cryohydrology are research methods, hydrological processes, watershed functions, and regional impact. The important characteristics of cryohydrology are frequent water phase transitions and high variability across spatial and temporal scales. Cryohydrology aims to deepen the understanding of the theoretical and cognitive levels of its mechanisms and processes, accurately quantify the hydrological functions of the basin, and promote understanding of the ecological and environmental impacts of the cryosphere.